Heart Management through Hypnosis-Based Interpersonal Communication Education for Employees of Q-Group Bengkulu City - Rachayu, Imma; Selviani , Diah; Suryani , Novi Ade; Yuniarti , Vemmi; Riefeldo (Universitas Dehasen Bengkulu, 2019)
This community service report aims to implement hypnosis-based interpersonal communication education in the management of the hearts of Q-Group employees in Bengkulu City. This research was conducted with the aim of increasing the emotional well-being and productivity of employees through the development of interpersonal communication skills and the use of hypnosis techniques.The method used in this research includes an initial survey to identify the needs and challenges of interpersonal communication faced by Q-Group employees. Furthermore, a hypnosis-based interpersonal communication education program was developed which was adapted to the characteristics of employees and their work environment. This program includes training in interpersonal communication skills, an introduction to hypnosis techniques, and the application of hypnosis in various communication situations.The results of this study are expected to provide real benefits for Q-Group employees in Bengkulu City in managing their emotions through more effective interpersonal communication. Hypnosis-based interpersonal communication education programs can be an effective step in building relationships among employees, improving work quality, and creating a harmonious work environment.